TEACHING SPEAKING SKILL TO DEAF STUDENTS - Sukrisna, Zahra Nurmeiliawati; Suryanti, Yanti; Rahmah, Mursidah (Journal of English Teaching and Linguistics Studies (JET Li), 2019)
ABSTRACT  English subject is taught to every student, including the special need students especially deaf students. This research aims to find out how the teacher teaches speaking skill as one of the skills in English to deaf students. Descriptive method is applied in this research which is conducted at SLB-B Dharma Wanita Bogor to 11th grade and the English teacher as the participants. Based on the result of this research, it is found that teacher has to apply the rules, strategies, and techniques in teaching speaking skill to deaf students. One of the ways in teaching them is teacher always helps them with the visual media since it helps them a lot in understanding the material. For example, teacher adds information by writing it on the whiteboard so they will know and understand how to sound the word clearly. Based on the result, it can be concluded that in teaching speaking skill to deaf students there are several special treatments and ways to be applied. They are; lip reading, counting the syllables, adding transcription, and mixing the languages. Keywords: Teaching Speaking Skill, Special Students, Deaf Students